Using Virtual Reality to Evaluate the Impact of Room Acoustics on Cognitive Performance and Well-Being - Doggett, Rachel; Sander, Elizabeth J.; Birt, James; Ottley, Matthew; Baumann, Oliver (Frontiers in Virtual Reality, 2021)
Irrelevant ambient noise can have profound effects on human performance and wellbeing. Acoustic interventions (e.g., installation of sound absorbing materials) that reduce intelligible noise (i.e., sound unrelated to the relevant speech, including noise from other talkers within the space) by reducing room reverberation, have been found to be an effective means to alleviate the negative effects of noise on cognitive performance. However, these interventions are expensive, and it is difficult to evaluate their impact in the field. Virtual reality (VR) provides a promising simulation platform to evaluate the likely impact of varied acoustic interventions before they are chosen and installed. This study employed a virtual classroom environment to evaluate whether an intervention to reduce reverberation can be simulated successfully in VR and mitigate the effects of ambient noise on cognitive performance, physiological stress, and mood. The repeated-measures experimental design consisted of three acoustic conditions: no ambient noise, typical open-plan classroom ambient noise without acoustic treatment, and the same ambient noise with acoustic treatment to reduce reverberation. Results revealed that ambient noise negatively affected participants’ cognitive performance but had no measurable effect on physiological stress or self-reported mood. Importantly, the negative effect of ambient noise was completely ameliorated by the acoustic treatment (i.e. indistinguishable from performance in the no noise condition). The study shows that VR provides an effective and efficient means to evaluate the cognitive effects of acoustic interventions.